2017
DOI: 10.5999/aps.2017.00451
|View full text |Cite
|
Sign up to set email alerts
|

Salvage of Unilateral Complete Ear Amputation with Continuous Local Hyperbaric Oxygen, Platelet-Rich Plasma and Polydeoxyribonucleotide without Micro-Revascularization

Abstract: In many cases of complete ear amputation, microvascular surgery is required for tissue perfusion and organ survival. However, microvascular reconstruction is not always feasible in the absence of suitable vessels. Here, we present the case of a 76-year-old man who underwent complete amputation of the left ear after a collapse at home because of cardiogenic syncope. He was treated with primary replantation and underwent a postoperative salvage course including continuous local hyperbaric oxygen therapy (HBOT), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Rather than DR, some authors support the choice of delayed reconstruction with costal cartilage following primary closure if microvascular repair is not possible. [ 9 25 26 ] If the avulsed ear is badly damaged, missing, or if the patient is unfit, primary closure of the defect with a secondary reconstruction can be a favorable option. [ 3 9 13 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than DR, some authors support the choice of delayed reconstruction with costal cartilage following primary closure if microvascular repair is not possible. [ 9 25 26 ] If the avulsed ear is badly damaged, missing, or if the patient is unfit, primary closure of the defect with a secondary reconstruction can be a favorable option. [ 3 9 13 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 34 35 ] In both an animal experimental model study and human cases, data suggest a benefit of HBO therapy to the survival of the re-attached auricular composite graft, even with large segment avulsion. [ 25 34 35 ] Furthermore, this treatment has demonstrated successful effects in minimizing the necrosis of pedicled flaps. [ 36 37 ]…”
Section: Resultsmentioning
confidence: 99%
“…Wound healing through activation of A 2A R is among the main pharmacological activities of Om- and Ok-PDRNs. Therefore, three clinical studies have been conducted to prove their wound healing properties [ 73 , 74 , 75 ]. Ok-PDRN was investigated as a potential therapeutic agent for the treatment of a chronic non-healing wound [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…PVRP along with continuous hyperbaric oxygen and polydeoxyribonucleotide was used in a unilateral complete ear amputation. It has been demonstrated that PVRP successfully salvaged almost the entire auricule [ 234 ]. It was confirmed in a randomized controlled clinical trial by Vozel et al that autologous PVRP is an effective treatment modality for chronic postoperative temporal bone cavity inflammation in patients whose disease could not be treated surgically to maintain serviceable hearing loss and a reasonable disease-related quality of life [ 74 ].…”
Section: Use Of Plasma Rich With Platelets and Extracellular Vesicles...mentioning
confidence: 99%